Penguatan Kompetensi Profesional Guru Berbasis Refleksi dan Best Practice (Studi di Sekolah Dasar Negeri Kota Cilegon) - Ifa Hafiroh; Harry Budiman; Inti Hujah; Eno Astriyani; Siti Laela (PT. Penerbit Tiga Mutiara, 2026)
This study was motivated by the low level of professional competence among elementary school teachers despite the fact that most teachers have obtained certification and adequate academic qualifications. Curriculum changes, advances in educational technology, and the demands of 21st-century learning require teachers to possess adaptive, reflective, and collaborative professional competencies. The research problem focused on the influence of reflective practice and best practice on the professional competence of teachers at A-accredited public elementary schools in Cilegon City. The study employed a quantitative approach with a causal-comparative design involving 105 teachers selected through proportionate stratified random sampling. Data were collected using Likert-scale questionnaires and analyzed through multiple linear regression using EViews 12. The results revealed that reflective practice had a positive and significant effect on teachers’ professional competence, with a t-value of 4.697 and a significance value of 0.000. Best practice also demonstrated a positive and significant effect, with a t-value of 5.065 and a significance value of 0.000. Simultaneous testing indicated that reflective practice and best practice jointly had a significant effect on teachers’ professional competence, with an F-value of 43.72 and a coefficient of determination of 52.2%. The findings confirm that reflective and collaborative cultures are capable of improving teachers’ professional quality continuously through learning evaluation, sharing teaching experiences, and developing innovative instructional strategies. The novelty of this study lies in the simultaneous examination of reflective practice and best practice through a quantitative approach within the context of A-accredited public elementary schools in Cilegon City. The findings also demonstrate that best practice exerts a greater influence than reflective practice on the professional competence of elementary school teachers.